Sistem Informasi Geograpfis dengan Google Map Untuk Pencarian Rumah Kost - Jenie Sundari; Dwi Arumaryawan (Jurnal Inovtek Polbeng Seri Informatika, 2018)
Abstract— Jakarta (DKI Jakarta) is the capital and largest city of Indonesia. In addition to the capital, Jakarta is the most populous city in Indonesia. In 2016, the population rose by 1.1 percent or 10.3 million inhabitants ((BPS DKI Jakarta). Jakarta City likened million hope, millions of people living in Jakarta to seek their fortunes, even many settlers from the area attended the University excels in Jakarta, because of the many newcomers who want to Jakarta led to increased needs house rental or rooms kos in Jakarta. Looking for kos to suit your needs is not easy, sometimes issues facing his difficult searching for a location near the place of work or place of lectures and an affordable price. With the utilization of technology through geographic information systems (GIS), to manage the existing boarding houses around Jakarta in the form of spatial information. The use of GIS who served in the form of the web, giving owners of boarding houses in informing the public and facilitate its location, in the search for the location of the boarding houses.Keywords: boarding houses, information, geographic, web